Bacteriophage therapy: A potentially effective tool in combatting tooth decay - Mehwash Kashif; Aman Ashar (Journal of the Pakistan Medical Association)
Caries of dental hard tissues is a multifaceted biofilm illness that spreads easily and occurs because of longstanding lowpH in the oral cavity. This causes the teeth to loose netamount of minerals and is the most prevalent healthcondition worldwide and a significant healthcare issue.1 Regular carbohydrate intake causes the biofilm microbiotain the mouth to change from its normal condition ofpreserving equilibrium to one that is acidogenic, aciduric,and cariogenic, which ultimately results in dental cavities.2 The biofilm, which is constantly active with low pHchanges, boasts the caries process.3 Unbalanced ecologyin the stable oral microbiome also leads to thedevelopment of caries. Significant variations in proteinexpression throughout time and under genetic controlseem to have an impact on the formation of biofilms.4